2021
DOI: 10.1029/2021jd036045
|View full text |Cite
|
Sign up to set email alerts
|

Ice and Supercooled Liquid Water Distributions Over the Southern Ocean Based on In Situ Observations and Climate Model Simulations

Abstract: Clouds play a crucial role in influencing Earth's radiation budget (Liou, 1992). The cloud types, height, the partition of cloud phases, and microphysical properties of liquid droplets and ice crystals are important in determining the cloud radiative effect (Chen et al., 2000;Matus & L'Ecuyer, 2017).Mixed phase clouds, clouds with the coexistence of liquid and ice, have been a focus of cloud microphysics research as many of their properties remain not fully understood (e.g., Korolev et al., 2017;Lohmann et al.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 66 publications
6
16
0
Order By: Relevance
“…The overestimation of ice phase clouds found at relatively warm temperatures in Yang et al. (2021) is consistent with the excessive ice at lower altitudes revealed in the present study. Intrigued by the comparable ice cloud biases over the Norwegian and Barents Sea in the Arctic, the suppression of deep convection initiation with the new trigger is found to substantially modify cloud microphysical processes for cloud liquid and ice.…”
Section: Evaluation Of Cloudssupporting
confidence: 92%
See 2 more Smart Citations
“…The overestimation of ice phase clouds found at relatively warm temperatures in Yang et al. (2021) is consistent with the excessive ice at lower altitudes revealed in the present study. Intrigued by the comparable ice cloud biases over the Norwegian and Barents Sea in the Arctic, the suppression of deep convection initiation with the new trigger is found to substantially modify cloud microphysical processes for cloud liquid and ice.…”
Section: Evaluation Of Cloudssupporting
confidence: 92%
“…It was also found that E3SMv1 tends to overestimate (underestimate) the occurrence frequency of ice phase clouds above (below) −20°C over the SO compared with in-situ observations during the SOCRATES (Southern Ocean Clouds, Radiation, Aerosol Transport Experimental Study) campaign (Yang et al, 2021). The overestimation of ice phase clouds found at relatively warm temperatures in Yang et al (2021) is consistent with the excessive ice at lower altitudes revealed in the present study. Intrigued by the comparable ice cloud biases over the Norwegian and Barents Sea in the Arctic, the suppression of deep convection initiation with the new trigger is found to substantially modify cloud microphysical processes for cloud liquid and ice.…”
Section: Clouds Over So and Antarcticsupporting
confidence: 88%
See 1 more Smart Citation
“…Figure 7 shows the probability of occurrence of liquid-phase, ice-phase, and mixed-phase clouds as a function of temperature. For the model data, mixed-phase cloud is defined as the liquid mass fraction between 0.1 and 0.9 (Yang et al, 2021). For the in situ measurement data, mixed-phase cloud is defined based on a phase identification algorithm (a combination of collocated airborne lidar, radar, and thermodynamic data) instead of liquid mass fraction (D'Alessandro et al, 2021;McFarquhar et al, 2021;Zaremba et al, 2020).…”
Section: Importance Of Sip To Southern Ocean Cloudsmentioning
confidence: 99%
“…Clouds cover 80%–90% of the SO region from an annual average perspective as indicated by satellite retrievals (Kay et al., 2012; Mace et al., 2009; Matus & L'Ecuyer, 2017; McCoy et al., 2014), making the SO one of the cloudiest regions on the Earth. Clouds over the SO are often mixed‐phase in nature, and the cloud lifetime, phase partitioning, and precipitation efficiency are strongly impacted by the number of ice crystals in these clouds (Liu et al., 2007; Mace et al., 2020; McFarquhar et al., 2021; Morrison et al., 2012; Vergara‐Temprado et al., 2018; Wilson et al., 2015; Yang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%